The Colonization Mission of Lithuanian Germans in 1942-1944: a Present from Germany or a Shot in the Eye? - Rec.: Arthur Hermann. Litauendeutsche als Kolonisten in Litauen 1942-1944. Annaberger Annalen. Nr. 17, 2009, S. 237-284 - Jakubavičienė, Ingrida (Lietuvos istorijos studijos, 2010)
-